Predicting median nerve depth from anthropometric features: A tool for safer invasive procedures - Sara Mogedano-Cruz; Ángel González-de-la-Flor; Cristina Rodríguez-Anadón; Lucimere Bohn; Jorge Villafañe; Carlos Romero-Morales (PLoS ONE, 2025)
Introduction The median nerve (MN) is frequently targeted in invasive procedures. Accurately locating its depth is essential to minimize complications. This study aimed to develop predictive models of MN depth based on anthropometric features. Design: cross-sectional observational study. Methods Fifty-three healthy adults (Men: 53%; Age range: 18–60 years) were evaluated. Sociodemographic (age and sex) and anthropometric data (height, weight, BMI, and proximal/mid-forearm circumference) were ascertained. Ultrasound was used to measure the depth of the MN relative to the skin and brachial artery at the elbow and mid-forearm. Hierarchical linear regression was applied to identify significant predictors of nerve depth. Results Men were significantly taller, heavier, and had a higher forearm circumference than women (p < 0.05 for all). Proximal forearm circumference strongly correlated with BMI and nerve depth. Regression analysis revealed it as a significant predictor of MN depth, explaining 49.4% (proximal) and 95.2% (mid-forearm) of the variance. The model for nerve-to-artery distance showed limited explanatory power (R2 = 0.164). Conclusion The mid-forearm circumference is a strong and accessible predictor of MN depth. The proposed models can support clinicians in estimating appropriate needle depth in ultrasound-guided procedures, potentially reducing the risk of nerve injury.